Perancangan Aplikasi Fuzzy Logic Untuk Prediksi Kasus Positif Covid-19 Menggunakan Metode Tsukamoto - Vani Maharani Nasution; Graha Prakarsa (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
COVID-19 is a virus that attacks the respiratory system which was first discovered in the Chinese city of Wuhan. This virus spreads very quickly and spreads throughout the world, including Indonesia. West Java is the province with the most positive cases of COVID-19, on May 4, 2020, 193 positive cases were added, and on 28 June 2020 there were 1,396 confirmed cases with an additional 18 patients. The unpredictable increase in positive cases of COVID-19 has led to the unpreparedness of officers in handling this outbreak. The West Java Provincial Health Office acknowledged the lack of Covid-19 handling facilities in 52 regional general hospitals in West Java Province to monitor positive COVID-19 patients, one of which was the lack of isolation rooms. In addition, the quality of the isolation room and personal protective equipment does not meet the standards. Predicting an increase or decrease in cases of positive COVID-19 patients needs to be done, so that there is readiness from the task force team for COVID-19 to deal with the problem of lack of facilities including isolation rooms and personal protective equipment. Fuzzy logic is one of the derivatives of artificial intelligence that is able to predict something. The research was conducted using the fuzzy logic of the Tsukamoto method through several stages including fuzzification, formation of rules, inference, and defuzzification. The results showed an error rate of 4.5% which indicated that predicting covid-19 using the fuzzy logic of the Tsukamoto method showed a high success rate